Era uma vez ... por onde anda Cinderela? : estudo de caso do Conto de Fadas Cinderela, na cidade de Maringá-PR - Martinelli, Marlise Maria Batista (2008)
The fairytales deal with themes that make part of the tradition of many people, because they discuss universal questions. Besides, they exemplify texts that are offered to readers in various moments of their lives, from the childhood to the adult life, allowing the creation of worlds of dream and imagination around and from texts. By the fact that the fairytales include a wide corpus, our search is limited in the study of the work Cinderella, as this one consolidated as one of the best known texts, because it is present, through re-editions, versions and adaptations in various literary and historic moments in all the world. Thereby, it becomes pertinent a case study of the said work, verifying not just the circulation of the tale, but mainly, the previous reading that some students and educators of the secondary education of a public school of Maringá have about fairytales and, in specific, of Cinderella tale. In order to achieve our objectives, we carried out, firstly, a bibliographic research that included reading conceptions, nature and functions of literature, reading sociology and fairytales. In a second moment, we carried out a survey and could find in libraries, bookstores and stores of old books a significant sample of the various means of circulation of the tale Cinderella. In the school scope, the used instruments were restricted to questionnaires applied to the students and educators of the researched school. Observing the individual, collective and social aspects of the readers, we carried out a survey about the fairytales and the work in question. Analyzing and confronting the obtained among the involved subjects, we noticed that the previous knowledge about the work is the same among students and educators. For them, the work with reading and with the fairytales is very important. However, observing the students' answers, such development gets intrinsically related with the teachers' position, what reflects some possible variables that took them to appreciate or reject the work. Such fact emphasizes that the mediation is fundamental for the reading be enlarged and diversified.